(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This study explores the evolving relationship between modern folklore and popular culture, with particular attention to how traditional stories, symbols, and motifs are reshaped and reimagined in today’s media landscape. It investigates how folklore adapts within digital environments, music, cinema, and social media, mirroring contemporary social values and shared identities. The research underscores the dual role of popular culture in both preserving and transforming folklore, as it revives ancient myths, legends, and folk themes through new artistic and cultural forms. By examining this interaction, the paper highlights the enduring importance of folklore in maintaining cultural continuity and inspiring creativity in the modern era.